Review on detection method, main source and geological application of diamondoids in crude oil - Fang, Chenchen; Hu, Guoyi; Yuan, Yilin; Gong, Deyu (Frontiers in Earth Science, 2023)
Diamondoids are alkanes with cage-like structure. Their diamond-like structure makes them have high stability and anti-biodegradability, and can be preserved and enriched in complex and long geological processes. Therefore, the continuous development of quantitative detection methods for diamondoids in crude oil has deepened the research of these compounds and made them more widely used in crude oil cracking evaluation, maturity evaluation, biodegradation evaluation and other aspects.